Investigating Flow State and Cardiac Pre-ejection Period During Electronic Gaming Machine Use - Murch, W. Spencer; Ferrari, Mario A.; McDonald, Brooke M.; Clark, Luke (Frontiers in Psychology, 2020)
Flow activities (e.g. sports, gaming) have been associated with positive affect and prolonged engagement. In the gambling field, modern Electronic Gaming Machines (EGMs, including modern slot machines) have drawn concern as a potentially flow-inducing activity that may be associated with gambling-related harms. Current research has heavily relied on self-reported flow, and further insights may be afforded by physiological methods. We present data from three separate experiments in which self-reported gambling flow and cardiac pre-ejection period (PEP; a measure of sympathetic nervous system arousal) were examined. Male undergraduate participants gambled on a genuine EGM in a laboratory setting for a period of at least 15 minutes, and completed the Flow subscale of the Game Experience Questionnaire. Aggregated data were analyzed using multilevel regression. Although EGM gambling was not associated with significant changes in PEP across participants, we found that self-reported flow states were associated with significant decreases in PEP during the first five minutes of EGM use. Thus, participants who experienced flow showed a greater sympathetic nervous system response to the onset of gambling. Though these effects were consistent in experiments 1 and 2, in experiment 3 the effect was inverted during the same time window. We conclude that flow during EGM gambling appears to be associated with early changes in sympathetic nervous system activity, but stress that more research is needed to characterize boundary conditions and moderating factors.